2015
DOI: 10.1039/c5cc05807d
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed new porphyrin-based small molecules as electron donors for highly efficient organic photovoltaics

Abstract: A series of unsymmetrical π-conjugated small molecules have been constructed from meso-alkyl substituted porphyrins as the central unit and 3-ethylrhodanine as the terminal group. Using PC71BM as an acceptor, and these small molecules as electron donors in solution-processed bulk-heterojunction solar cells, a high power conversion efficiency of 6.49% has been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Nowadays, one of the most efficient strategies for optoelectronic materials is to design and synthesize donor-acceptor molecular systems containing a π-bridged(D-π-A) framework [15][16][17][18]. The electronic energy levels, absorption and emission spectra, intermolecular stacking, and film morphology can be tuned effectively through chemical modification of the acceptor, donor, and π-bridge fragments [19][20][21]. Amongst various small molecular material building blocks, such as benzofuran [22], triphenylamine (TPA) units [23], tetraphenylethylene (TPE) [24], selenophene [25], phenanthrene [26], pyrene [27], and diketopyrrolopyrrole (DPP) derivative, DPP derivatives have attracted much interest owing to their outstanding performance in OSCs, OLEDs, and FETs [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, one of the most efficient strategies for optoelectronic materials is to design and synthesize donor-acceptor molecular systems containing a π-bridged(D-π-A) framework [15][16][17][18]. The electronic energy levels, absorption and emission spectra, intermolecular stacking, and film morphology can be tuned effectively through chemical modification of the acceptor, donor, and π-bridge fragments [19][20][21]. Amongst various small molecular material building blocks, such as benzofuran [22], triphenylamine (TPA) units [23], tetraphenylethylene (TPE) [24], selenophene [25], phenanthrene [26], pyrene [27], and diketopyrrolopyrrole (DPP) derivative, DPP derivatives have attracted much interest owing to their outstanding performance in OSCs, OLEDs, and FETs [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Additionally, the intermolecular stacking, lm morphology, and charge transport properties can be determined by the type and length of side chains of D-A molecular structures. 28,29 It has been reported that a…”
Section: Introductionmentioning
confidence: 99%
“…[20] For example, POR-based photosensitizers are among the best sensitizers in dye sensitized solar cells (DSSCs). In recent years, remarkable progress has been made on using POR as the main donor moieties [21][22][23][24][25][26] and efficiencies as high as 8% have been reached in SMOSC [27] devices while in DSSC systems efficiencies close to 12% have been described. [28] Recently, we described two similar conjugated acceptor-donor-acceptor (A--D--A) compounds that also contained a Zn-porphyrin but were capped by dicyanovinylene groups as acceptor units -these materials gave a photoconversion efficiency (PCE) of 3.21%.…”
Section: Introductionmentioning
confidence: 99%